Improving Vocational Embroidery Decoration Wall Skills Through Learning By Doing Model for Autistic Children in SLB Autisma YPPA Padang - Esti Wahyuningsih; Yarmis Hasan (EDUCATIO : Journal of Education, 2019)
This study discusses three students who have problems in vocational skills, making wall decoration creations. The observation shows that students have good interest and talent in embroidery. The purpose of this paper is to improve vocational skills to make creations of wall hangings through the learning model of learning by doing. The research method used was classroom action research consisting of two cycles. Each cycle consists of four meetings held in several stages, namely planning, implementing actions, observing, and reflecting. Data collection techniques used were observation, documentation, and tests. The results showed that the vocational learning process of making wall hangings creations for children with Class X autism was carried out through learning by doing learning models. The results of the study in the first cycle have increased. At the first meeting until the fourth meeting TQ scored 42.8%, 54.7%, 54.7%, and 61.9%, UM earned 47.6%, 59.5%, 59.5%, and 66.6%, and NA 52.3%, 61.9%, 61.9% and 69%. In the second cycle, TQ scored 69%, 69%, 73.8%, and 80.9%, UM earned 76.1%, 76.1%, 78.5%, and 80.9%, and NA received 85.7%, 85.7%, 90.4%, and 90.4%. The conclusion is that the implementation of embroidery wall hanging vocational skills can be improved through the learning model of learning by doing